Boosting ESL Vocabulary: The Role of Interactive Method in Language Acquisition - Yuli Ari Sandy; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study investigated the effectiveness of interactive methods in enhancing vocabulary acquisition among English as a Second Language (ESL) students. Focusing on innovative teaching strategies, the research examined how interactive activities such as games, role-playing, and technology-assisted learning affect vocabulary retention and use. The research question is "What is the impact of the interactive method on the students' vocabulary enhancement?" There were 100 students of Marine Cruise Yogyakarta, Sukoharjo Branch, who were selected for this research. The data collection method was mixed method through open-ended questionnaire, observation, and interview. Descriptive narrative research design was used to analyze the data through triangulation. The result showed that interactive method significantly contribute to vocabulary enhancement in learning English as a Second Language (ESL) especialy in; 1) student engagement, 2) integration of technology, 3) collaborative learning. This research provides valuable insights for educators seeking to implement effective strategies for teaching vocabulary in ESL classrooms.